A liderança no contexto da gestão cultural: um estudo sobre o grupo THOLL/RS - Vargas, Charles da Rocha de (2015)
The leadership in businesses and cultural organizations is undergoing a process of change. The professional becomes a requirement for survival. Leading a team, these days, due to differences among generations, high competition, economic difficulties, among other things, have demanded that cultural organizations had the clarity that for their survival, it was necessary to change their leadership model. The need for a leadership based on the leader’s self-knowledge, in servitude, and the understanding that we need to know how to understand the thinking model of led groups, focuses necessarily on getting better results. Within this context is the Tholl Group of Pelotas / RS, formed in 1987 as a circus troupe, became one of the cultural heritage of Rio Grande do Sul State, bringing joy, smile, art and the circus to thousands of people throughout Brazil. Its management model is a case study. After all, the group remains active for almost thirty years, being successful in various parts of Brazil. Thus, this dissertation, qualitative in nature, aims to analyze the leadership model in the context of cultural management, taking as a case study the Tholl Group. Data collection used as main sources documentary research and semi-structured interviews. To compose the data analysis, content and thematic analysis were employed. The results of this study show specifically: (a) that the intervention process provided that leaders implemented a selfknowledge process, by learning about their selves and their leadership model; (b) that the leadership and the group are still very dependent on their founder; (c) the need for this work to have a continuity, so that leaders can continue to develop; (d) the need for the group to find its own management model, in order to improve the administrative aspect.